Russia and the Syrian conflict Moscow's domestic, regional and strategic interests - Kozhanov, N. A. (Nikolaĭ Aleksandrovich) 1982- (Gerlach Press, 2016)
This book is the first to offer a comprehensive survey of Moscow's foreign policy interests in Syria. The author considers the Kremlin's diplomacy on Syria within the broader system of Russian foreign policy in the Middle East; he analyses the influence of Russian domestic dimensions on Moscow's approaches to the subject; and he considers how Moscow's priorities in Syria have evolved during the last five years and what factors influenced this evolution. Key factors considered include: Russian presence in the Middle East before and after the fall of the Soviet Union; The challenge of the Arab Spring; Why it was so important to save Assad; How serious is the jihadist threat for Russia; Russian military involvement in the Syrian conflict: what will be the outcome?; Significance of Moscow's military intervention in the wider Middle East context.